Adding prebiotic in cereal bars: physico-chemical characterization and sensory acceptability among practitioners of martial arts - Serbai, Daiane; Reis Ballard, Cíntia; Manhani, Maria Raquel; Freitas dos Santos, Elisvânia; Novello, Daiana (O Mundo da Saúde, 2016)
The objective this study was to verify the sensory acceptability of cereal bars added inulin between practitioners of martial arts. Also, to determine the physico-chemical composition of the standard formulation and that more inulin content and standard similar to acceptance. Five formulations were prepared cereal bars: F1 (standard with 0% inulin) and the other containing 2% (F2), 4% (F3), 6% (F4) and 8% (F5) inulin. Participated in the sensory evaluation 100 untrained panelists, of both genders, aged between 18 and 60 years. The physico-chemical analysis evaluated the moisture, ash, protein, lipids, carbohydrates, calories and dietary fiber content. There was no significant difference (p>0.05) between samples for appearance, aroma and color attributes. However, F5 had lower acceptability than the standard formulation in taste and texture attributes, and global acceptance and purchase intent. Considering this context, F4 was the sample with the highest inulin content and similar acceptance to the standard in most of the evaluated attributes being selected along with the standard formulation for evaluation of physico-chemical composition. There was no difference between the moisture, ash, protein and lipids content to the standard formulation and F4. Lower content of calories and higher carbohydrate and dietary fiber were found in F4 comparing it with the standard sample. It is concluded that a level of addition of up to 6% inulin into the cereal bars was well accepted by tasters to give sensory acceptance similar to standard product with good market expectation.